OP43 Explaining High Parenting Stress in the Growing Up in Scotland Study for Mothers with Both High and Low Educational Levels: The Role of Employment and Social Support for Parenting. (10th September 2013) - Parkes, A; Sweeting, H; Wight, D
Abstract : Background: Stresses associated with raising a child may lead to less optimal parenting, with consequences for children's development. Parent's employment and receipt of social support may impact on stress differently according to family affluence. Affluent parents may be most pressured when balancing employment with child-related commitments. They may also have relocated, restricting informal support. Disadvantaged parents commonly report barriers to accessing formal parenting support and are more likely to have experienced family break-up, also restricting informal support. This study explores how aspects of employment and social support are associated with parenting stress among mothers grouped according to educational level. Methods: Data were collected from mothers in the Growing up in Scotland study interviewed when their child was 10 months (N = 5870 out of 6127 main carers contacted in 2011/12). Parenting stress was self-reported using an abbreviated version of the Parental Stress Scale. "High stress" was defined as the bottom quartile of stress scores. Results: 33% of mothers were educated to degree level, 59% had lesser qualifications and 7% none. High stress was more likely among both degree-educated mothers (OR 1.15 [95% CI 1.02, 1.30]) and those with no qualifications (1.60 [1.23, 2.08]), compared to mothers with lesser qualifications. More degree-educated mothers worked full-time (36%) compared to those with lesser (13%) or no (6%) qualifications, but work patterns did not explain stress differences. More mothers with degrees (30%) or no qualifications (31%) were born outside Scotland compared to those with lesser qualifications (13%). High stress levels were greater among degree-educated 'incomers' (1.60 [1.34, 1.90]) than mothers with lesser qualifications, but did not differ between native degree-educated mothers and those with lesser qualifications. When compared to mothers with lesser qualifications, odds of high stress among degree-educated 'incomers' reduced (1.21 [0.90, 1.62]) after adjustment for difficulty arranging childcare and less frequent contact with friends and the child's grandparents. Incomer status, childcare problems and frequency of informal support did not explain stress among mothers with no qualifications. Low awareness of and/or receptivity to formal support, and feeling less close to family/friends, attenuated odds of stress for this group to 1.30 (0.97, 1.72). Conclusion: Parenting stress in degree-educated mothers born outside Scotland was related to childcare problems and more generally to less frequent informal support. Among mothers with no qualifications, fewer close informal ties and more perceived barriers to formal support were associated with stress. Findings suggest different approaches to parenting support are appropriate for different social groups.